PEMBERIAN BUAH PEPAYA (Carica papaya) TERHADAP TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI - Wahdi, Achmad; Puspitosari, Dewi Retno (Jurnal LENTERA, 2024)
Hypertension in the elderly occurs due to decreased elasticity of the arteries during the aging process. According to previous research, papaya fruit can lower blood pressure in adult patients. The aim of giving papaya fruit is to reduce blood pressure in elderly people with hypertension. Method of providing education about the benefits of papaya for reducing blood pressure in 15 elderly people with hypertension RT. 003.RW. 002, Kalianyar Village. Results of counseling on giving papaya to reduce blood pressure in elderly people with hypertension in RT. 003.RW. 002, Kalianyar Village, Nganjuk Regency, before being given counseling on mild hypertension it was 33.3% and after being given counseling it was 66.7% mild hypertension, elderly people with hypertension can use papaya fruit to lower blood pressure which does not cause side effects in lowering blood pressure. In conclusion, giving papaya fruit can reduce blood pressure in RT. 003.RW. 002, Kalianyar Village, Nganjuk Regency, so the elderly are advised to consume papaya to lower blood pressure without causing side effects.